2014
DOI: 10.1055/s-0034-1384674
|View full text |Cite
|
Sign up to set email alerts
|

Muscle versus Fasciocutaneous Free Flaps in Heel Reconstruction: Systematic Review and Meta-Analysis

Abstract: The current review provided a summary of reported outcomes of free heel reconstruction in the literature till date. With the current evidence largely limited to small cohort studies (level IV evidence), there were no significant differences found between reconstructive options. These findings serve as a call to action for more reconstructive surgeons to collaborate on multi-institutional prospective studies with robust outcomes assessment. As such, an ideal flap for reconstruction of the weight-bearing heel ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 18 publications
3
66
1
Order By: Relevance
“…But as previous reports show that there is no significant difference in flap survival in regard to the flap type. 25 Nevertheless, further study may be warranted to see the outcome for reconstruction on ischemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…But as previous reports show that there is no significant difference in flap survival in regard to the flap type. 25 Nevertheless, further study may be warranted to see the outcome for reconstruction on ischemic regions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the skingrafted surface of muscle flap remains inferior in the weightbearing areas and prone for recurrent ulceration requiring secondary procedures and specialized footwear. 12,13 Fasciocutaneous flap with minimal fascia around its pedicle essentially contains adequate fat and skin paddle that provide good cushioning effect akin to the native fat pad and superior surface for walking than split-thickness skin graft. The fascia, if preserved, not only provides poor vascular structure on the floor of ulcer but also results in feeling of walking on a slippery surface.…”
Section: Discussionmentioning
confidence: 99%
“…Other options for soft-tissue reconstruction of the heel include the free latissimus dorsi and the radial artery forearm flaps. 34,35 Peek et al 5 reported one complete flap loss of two patients who underwent heel reconstruction with the free iliac crest transfer. Nevertheless, both patients regained adequate mobility.…”
Section: Discussionmentioning
confidence: 99%